Guess the Picture Method A Solution for Mastering Arabic Vocabulary at Samakke Islam Wittaya School, Satun, Thailand. - Azizah, Karimatul; Asy'ari, Hasyim; Istiqomah, Rofiatul (Al-Fusha : Arabic Language Education Journal, 2025)
This research aims to find out and understand how effective the “Guess the Picture” method is in teaching Arabic at Samakke Islam Wittaya School in Satun, Thailand. The research uses a qualitative approach with a case study to explore how this method is used in teaching Arabic vocabulary (mufrodat) at the school. Data was collected through observation, interviews, and documentation. The data analysis had two main steps: reducing the data and content analysis. The results showed that Arabic learning at this Islamic school in Thailand uses the “Guess the Picture” method. In this method, the teacher shows picture cards and says the Arabic vocabulary repeatedly. Once the students can pronounce the words correctly and fluently, they are asked to guess the picture in Arabic. Then, they are asked to stick the correct vocabulary card on the board to match the picture. This kind of game helps students who have difficulty memorizing Arabic vocabulary and makes learning more fun and less boring.